COVID-19 Lockdown: A Review of an Alternative to the Traditional Approach to Research - Adom, Dickson; Osei, Mavis; Adu-Agyem, Joe (Research Journal in Advanced Social Sciences, 2020)
This study aims to offer alternative ways of conducting research in the periods of lockdown due to the COVID-19 pandemic when the traditional research approaches are not feasible. This is crucial as some researchers hold the wrong perception that such difficult times are only fallow periods to focus on their personal and family problems. The study argues that there is the need for researchers to be busy carrying out investigations aimed at finding solutions to the multiplicity of problems faced by global communities as a result of the pandemic. Using desk research and document analysis of secondary data from published articles, the study discusses research approaches, particularly, alternative means of garnering primary and secondary data for investigating the COVID-19 pandemic from different academic disciplines. It posits that telephone and video conferencing interviews, text-based chats and e-surveys are alternative means for collecting primary data while secondary data from published articles and newspaper reports are viable means of generating reliable data for research. These alternative approaches to research would keep researchers busy in finding solutions to the difficult challenges faced during pandemics, the period their services are needed the most.